2014
DOI: 10.1364/ol.39.001481
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of spectral correlation control in a source of polarization-entangled photon pairs at telecom wavelength

Abstract: Spectrally correlated photon pairs can be used to improve performance of long range fiber based quantum communication protocols. We present a source based on spontaneous parametric down-conversion producing polarization entangled photons without spectral filtering. In addition, the spectral correlation within the photon pair can be controlled by changing the pump pulse duration or coupled spatial modes characteristics. The spectral and polarization correlations were characterized. The generated photon pairs fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Such a quantum state engineering method can be realized by considering the group-velocity-matched (GVM) condition in specific crystals at certain wavelengths [4][5][6]. Previous work in the field has shown that the GVM condition can be realized in several crystals, e.g., KDP crystal at 830 nm [1,2,7], periodically poled KTP crystal (PPKTP) at 1584 nm [5,8] and BBO crystal at 1514 nm [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Such a quantum state engineering method can be realized by considering the group-velocity-matched (GVM) condition in specific crystals at certain wavelengths [4][5][6]. Previous work in the field has shown that the GVM condition can be realized in several crystals, e.g., KDP crystal at 830 nm [1,2,7], periodically poled KTP crystal (PPKTP) at 1584 nm [5,8] and BBO crystal at 1514 nm [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Another solution is to adapt the pump laser spectrum and the dispersion properties of the non-linear material. This approach has been implemented in various media such as bulk crystals [12][13][14], waveguides [15,16], or fibers [17]. Quantum communication requires narrowband sources and recent focus has shifted to using periodically poled potassium titanyl phosphate (PPKTP) nonlinear crystals with ps pulsed lasers [18][19][20][21][22][23] to address these demands of quantum communication.…”
Section: Introductionmentioning
confidence: 99%
“…Optical elements are dispersive and cause unwanted modification of the photons' temporal characteristics. The deteriorating dispersion effects can be reduced by using photon pairs that are spectrally narrow and feature appropriate spectral correlations [16][17][18].The spectra of SMF coupled photon pairs generated in SPDC process can be negatively [19,20], positively [16][17][18][21][22][23] or not correlated at all [24][25][26]. The effect of negative correlation originates from the energy conservation relation and is a consequence of pumping by a continuous wave (CW) laser.…”
mentioning
confidence: 99%
“…Uncorrelated spectra can be achieved in a nonlinear crystal by using a pulsed laser pump with careful setup parameter choice or by using narrow spectral filters. However, for positive correlation, an additional requirement of group velocity matching needs to be fulfilled [21].Here we perform numerical analysis of the SPDC photon pair source experimentally analyzed in Refs [17,18], which is schematically depicted in Fig. 1.…”
mentioning
confidence: 99%